2008
DOI: 10.1016/j.jaci.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

IKBKG (nuclear factor-κB essential modulator) mutation can be associated with opportunistic infection without impairing Toll-like receptor function

Abstract: Background-Patients with hypomorphic nuclear factor-κB essential modulator (NEMO) mutations have extensive phenotypic variability that can include atypical infectious susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Between 2002 and 2016, 13 patients with XL-EDA-ID were reported to have undergone HSCT (Dupuis-Girod et al 2002;Orange et al 2004;Tono et al 2007;Mancini et al 2008;Pai et al 2008;Salt et al 2008;Fish et al 2009;Minakawa et al 2009;Permaul et al 2009;Imamura et al 2011;Kawai et al 2012;Abbott et al 2014;Carlberg et al 2014;Klemann et al 2016). A summary of patient characteristics prior to HSCT can be found in Table 1.…”
Section: X-linked Ectodermal Dysplasia With Immunodeficiencymentioning
confidence: 99%
“…Between 2002 and 2016, 13 patients with XL-EDA-ID were reported to have undergone HSCT (Dupuis-Girod et al 2002;Orange et al 2004;Tono et al 2007;Mancini et al 2008;Pai et al 2008;Salt et al 2008;Fish et al 2009;Minakawa et al 2009;Permaul et al 2009;Imamura et al 2011;Kawai et al 2012;Abbott et al 2014;Carlberg et al 2014;Klemann et al 2016). A summary of patient characteristics prior to HSCT can be found in Table 1.…”
Section: X-linked Ectodermal Dysplasia With Immunodeficiencymentioning
confidence: 99%
“…With regard to fungal disease, patients with IKBA mutations are universally affected by CMC and 60% of them develop PCP (Picard et al 2011); decreased numbers of IL-17 þ T cells have been reported in these patients (Schimke et al 2013). Instead, CMC and PCP are far less common in NEMO-deficient patients (,10%) (Salt et al 2008;Picard et al 2011). Both EDA-ID syndromes belong in the heterogeneous group of disorders termed hyper-IgM syndromes (HIGM), characterized by elevated IgM despite hypo-g-globulinemia as a result of defects in immunoglobulin class switch recombination.…”
Section: Anhidrotic Ectodermal Dysplasia With Immunodeficiency (Eda-id)mentioning
confidence: 99%
“…Clinical and laboratory features were previously reviewed and were significant for the absence of the somatic problems of oligodontia, ectodermal dysplasia or chronic gastrointestinal (GI) disease. 5 Despite both impaired natural killer (NK) cell function and impaired T-cell receptor (TCR) signaling, Toll-like receptor (TLR) signaling appeared to be intact. 5 The patient received a myeloablative conditioning regimen consisting of BU, CY and equine antithymocyte globulin (ATG) followed by 10/10-matched, unrelated umbilical cord blood allo-HSCT.…”
mentioning
confidence: 99%
“…5 Despite both impaired natural killer (NK) cell function and impaired T-cell receptor (TCR) signaling, Toll-like receptor (TLR) signaling appeared to be intact. 5 The patient received a myeloablative conditioning regimen consisting of BU, CY and equine antithymocyte globulin (ATG) followed by 10/10-matched, unrelated umbilical cord blood allo-HSCT. Post transplant, the patient developed allergies to sulfa and walnuts but did not develop chronic GI symptoms.…”
mentioning
confidence: 99%